Octreotide Conjugates for Tumor Targeting and Imaging - Figueras, Eduard (Pharmaceutics, 2019)
Tumor targeting has emerged as an advantageous approach to improving the efficacy and safety of cytotoxic agents or radiolabeled ligands that do not preferentially accumulate in the tumor tissue. The somatostatin receptors (SSTRs) belong to the G-protein-coupled receptor superfamily and they are overexpressed in many neuroendocrine tumors (NETs). SSTRs can be efficiently targeted with octreotide, a cyclic octapeptide that is derived from native somatostatin. The conjugation of cargoes to octreotide represents an attractive approach for effective tumor targeting. In this study, we conjugated octreotide to cryptophycin, which is a highly cytotoxic depsipeptide, through the protease cleavable Val-Cit dipeptide linker using two different self-immolative moieties. The biological activity was investigated in vitro and the self-immolative part largely influenced the stability of the conjugates. Replacement of cryptophycin by the infrared cyanine dye Cy5.5 was exploited to elucidate the tumor targeting properties of the conjugates in vitro and in vivo. The compound efficiently and selectively internalized in cells overexpressing SSTR2 and accumulated in xenografts for a prolonged time. Our results on the in vivo properties indicate that octreotide may serve as an efficient delivery vehicle for tumor targeting.